Comparative analisys of three different diagnostic methods to evaluate carious activity in a community basis Análise comparativa de três métodos de diagnóstico de atividade cariosa em âmbito coletivo - Luciana Cardoso; Lisiane Christoff Corrêa de Barros; Paulo Floriani Kramer; Cassiano Kuchenbecker Rösing; Carolina Covolo da Costa (University of São Paulo, 2005)
The present research has made a comparison between three distinct methods to evaluate carious activity in a community basis. The studied method was based in a modified DMFS/dmfs index including non-cavitated lesions. Two factors were analyzed: the possible reproduction of the inclusion of carious activity criteria and the presence of bacterial plaque. Thus, the three study groups presented with plaque, after supervised self-performed plaque removal with dental toothbrush and without plaque after professional prophylaxis, which corresponded to three diagnostic methods. The three exams took place one week apart from each other. For this analysis, a modified DMFS/dmfs index was proposed with alterations in diagnostic criteria due to the inclusion of carious activity parameters. The study was performed in a group of 30 children aged 11 years old. According to the results, the diagnostic method for carious activity in the three situations was reproducible and can be considered a proper approach to perform caries diagnosis in a community basis. Este trabalho realizou uma comparação entre três métodos distintos para avaliação da atividade cariosa em âmbito coletivo. Os métodos estudados foram baseados em um CPOS/ceos modificado, com inclusão de lesões não cavitadas. Os fatores estudados foram a possibilidade de reprodutibilidade da inclusão de critérios de atividade cariosa, bem como a presença de placa bacteriana. Portanto, os três grupos avaliados apresentavam-se com placa bacteriana; com remoção de placa bacteriana pelo próprio paciente (sob supervisão) com escova dental e sem placa bacteriana, após profilaxia profissional, que correspondiam aos três métodos de diagnóstico. Os três exames foram realizados com intervalo de uma semana entre cada um. Para esta análise, propõe-se um índice CPOS/ceos modificado com alterações nos critérios de diagnóstico através da inclusão de parâmetros de atividade de doença. O estudo foi realizado em um grupo de 30 crianças, com idade de 11 anos. De acordo com os resultados obtidos, os três métodos de diagnóstico de atividade cariosa, na população estudada, demonstraram-se reproduzíveis, podendo ser mais uma forma de adequadamente realizar-se diagnóstico de cárie em nível coletivo.